Sprout-AI: Image-Based Plant Disease Detection Mobile Application - Mohamad Sulaiman, Nur Aisyah; Ezam Shah, Nur Farhah Ain; Norhashim, Nur Zulaikha; Berahim, Mazniha (Multidisciplinary Applied Research and Innovation, 2025)
This project aims to produce an image-based plant disease detection mobile application, Sprout-AI designed to revolutionize plant disease management for farmers and gardeners. While existing solutions on market provide basic plant’s support, Sprout-AI goes further and provides comprehensive information and interactive support. Leveraging advanced image detection and an AI-powered chatbot, Sprout-AI provides accurate disease detection, personalized treatment recommendations, and ongoing plant care guidance. The biggest challenge Sprout-AI addresses is the lack of accessible information about plant diseases, which hinders effective plant care. By integrating machine learning models for real-time image detection, Sprout-AI enables users to quickly detect and control plant diseases. The AI chatbot improves the user experience by providing tailored advice and addressing specific questions. Developed using the ADDIE model, Sprout-AI goes through rigorous analysis, design, development, implementation and evaluation phases to ensure functionality and effectiveness. Combining advanced technology with user-centered design, Sprout-AI emerges as a comprehensive solution for managing plant health and improving agricultural outcomes.